Zeolite Synthesis from Natural Kaolin: The Effect of Metakaolin Heating and Transformation - Zawati Harun; Faiz Hafeez Azhar; Wan Nur Farah Atikah Hanafi; Norsuhailizah Sazali; Rosniza Hussin; Zakiah Kamdi; Ainun Rahmahwati Ainuddin; Muhamad Zaini Yunos; Anuar Ismail (Emerging Advances in Integrated Technology, 2024)
In this study, the effect of kaolin heating and metakaolin transformation on zeolite synthesis was investigated. Two different metakaolin temperatures at the early stage of transformation were chosen in determining the lowest temperature that was capable of synthesizing the zeolite structure from natural kaolin. The synthesis of zeolite materials from the transformation of natural kaolin to metakoalin was conducted through the hydrothermal method. Natural kaolin obtained from Ipoh, Perak, was calcined at two different calcination temperatures of 600°C and 650°C. Metakaolin was obtained after 2 hours of exposure at 600°C and 650°C, respectively, with slightly different FTIR peaks of quartz at both temperatures. The incomplete metakaolin formation at a slightly lower temperature revealed the unsuccessful zeolite formation. At slightly higher calcination temperatures, the metakoalin peak obviously existed and led to the formation of the complete zeolite phase. This experiment also proved the importance of accurate calcination temperature in converting to zeolite synthesis. Furthermore, this current work also revealed that the complete transformation of metakoalin that can be conducted slightly lower temperature as compared to the common metakoalin phase will minimize energy consumption during the zeolite synthesis as well as the metakoalin transformation.